2006
DOI: 10.1152/ajpheart.00523.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell adhesion to cardiac microvascular endothelium: activators and mechanisms

Abstract: . Mesenchymal stem cell adhesion to cardiac microvascular endothelium: activators and mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(146 citation statements)
references
References 32 publications
5
137
0
1
Order By: Relevance
“…Existing data suggest that the cytokines IL-1b and TNF-a activate adherence properties of the MSC including the upregulation of the VCAM-1-VLA-4 adhesion pathway. 48 Additional receptors known to be upregulated by TNF-a priming include CCR3 and CCR4; these findings correlate with the observation of increased in vitro migration to RANTES (a CCR3 ligand) and macrophage-derived cytokine (MDC (CCL22)-a CCR4 ligand). 3 Several growth factors have been shown to induce MSC migration.…”
Section: Activation Of Msc With Proinflammatory Cytokines (That Is Tmentioning
confidence: 53%
“…Existing data suggest that the cytokines IL-1b and TNF-a activate adherence properties of the MSC including the upregulation of the VCAM-1-VLA-4 adhesion pathway. 48 Additional receptors known to be upregulated by TNF-a priming include CCR3 and CCR4; these findings correlate with the observation of increased in vitro migration to RANTES (a CCR3 ligand) and macrophage-derived cytokine (MDC (CCL22)-a CCR4 ligand). 3 Several growth factors have been shown to induce MSC migration.…”
Section: Activation Of Msc With Proinflammatory Cytokines (That Is Tmentioning
confidence: 53%
“…2B, 18Co cells were treated overnight with TNF-␣ at varying concentrations (0 -80 ng/ml), followed by treatment with LPA (10 M) for 4 h. Increases in COX-2 protein expression were evident at a TNF-␣ concentration as low as 0.8 ng/ml, well within physiological levels, and persisted at a concentration of 80 ng/ml. Based on this data, subsequent experiments were performed using TNF-␣ at a concentration of 8 ng/ml, well within the range of concentrations used in other studies (12,26,41,61). In Fig.…”
Section: Lpa and Tnf-␣ Lead To Synergistic Cox-2 Expression In 18co Cmentioning
confidence: 88%
“…Electron microscopy revealed that, even after 30 min of perfusion, approximately 30% of the perfused MSC had transmigrated across the endothelium -this percentage rose to 50% after 60 min but remained constant thereafter (Schmidt et al, 2006). Elsewhere, transmigration across the endothelium into cardiac tissue of MSC injected into the ventricular cavity has been observed in rats pre-treated with TNF-a or in rats 24 h after ischaemia (30 min)-reperfusion injury (Segers et al, 2006). Whilst the adhesion molecules and mechanisms involved in MSC diapedesis are, as yet, unclear, the molecules identified to date that regulate the various other stages of MSC recruitment from the blood stream to the surrounding tissues, summarised in Fig 1, have furthered our understanding of this process and extended our appreciation of the ability to administer MSC systemically as a potential therapeutic strategy.…”
Section: +mentioning
confidence: 99%
“…. The process of MSC transendothelial migration appears to be similar to that of leucocytes and HSC, albeit under the control of specific adhesion molecules elucidated largely by Ruster et al (2006); Segers et al (2006) and Schmidt et al (2006). 1 Has been shown to be inhibited by: a neutralising P-selectin antibody, fucosidase or O-sialoglucoprotein-endopeptidase treatment of MSC, the absence of Ca 2+ /Mg…”
Section: Integrins and Their Role In Msc Firm-adhesion And Transendotmentioning
confidence: 99%